2013
DOI: 10.1007/s10439-013-0880-9
|View full text |Cite
|
Sign up to set email alerts
|

Off-line and On-line Stress Detection Through Processing of the Pupil Diameter Signal

Abstract: The pupil diameter (PD), controlled by the autonomic nervous system, seems to provide a strong indication of affective arousal, as found by previous research, but it has not been investigated fully yet. In this study, new approaches based on monitoring and processing the PD signal for off-line and on-line "relaxation" vs. "stress" differentiation are proposed. For the off-line approach, wavelet denoising, Kalman filtering, data normalization, and feature extraction are sequentially utilized. For the on-line ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…18,19 Other studies have shown that pupil size can also be affected by the level of arousal, 20 the transient allocation of attention during which the pupil shows transient dilation, 21,22 a type of stress reaction. 23 Yet, since our study deals with the progression of relative changes with respect to a light-adapted baseline, we believe that we have observed a clear pattern of a relatively fast initial increase, and then a slower decrease in pupil size, as long as the arousal factor was controlled and fixation was present.…”
Section: Discussionmentioning
confidence: 70%
“…18,19 Other studies have shown that pupil size can also be affected by the level of arousal, 20 the transient allocation of attention during which the pupil shows transient dilation, 21,22 a type of stress reaction. 23 Yet, since our study deals with the progression of relative changes with respect to a light-adapted baseline, we believe that we have observed a clear pattern of a relatively fast initial increase, and then a slower decrease in pupil size, as long as the arousal factor was controlled and fixation was present.…”
Section: Discussionmentioning
confidence: 70%
“…The pupil can constrict to 1.5 mm in diameter or dilate to about 8-9 mm depending on the predominant activation of parasympathetic or sympathetic nervous system. Since an increase in the sympathetic activity promotes pupil dilation (Bradley et al, 2008), pupil dilation has also been employed as a physiological marker of sympathetic nervous activation and stress induction (Yamanaka and Kawakami, 2009;Ren et al, 2014).…”
Section: Pupil Sizementioning
confidence: 99%
“…Another study found that pupil diameter increased when viewing emotional pictures, regardless of their valence, and that this correlated with GSR, suggesting that pupil diameter increase is sympathetically mediated (Bradley et al, 2008). It can also be used for the detection of pain, for instance, in non-communicative patients (Ren et al, 2014). Pupil dilatation can now easily be measured with special glasses or cameras, even in an unobtrusive way (Petridis et al, 2013).…”
Section: Some Potentially Useful Physiological and Neurological Indicmentioning
confidence: 99%
“…However, GSR lacks specificity because elevated levels of GSR are not always the result of stress, since other factors (such as temperature) may also result in an increased GSR (Bakker et al, 2011). Therefore, more recently, pupillometry has been proposed as a more effective and robust parameter for detection of stress (Ren et al, 2014).…”
Section: Some Potentially Useful Physiological and Neurological Indicmentioning
confidence: 99%